EFEKTIFITAS TERAPI MUSIK KLASIK MOZART TERHADAP PENURUNAN GEJALA POST PARTUM BLUES - Ike Dwi Permatasari; Misrawati ' '; Oswati ' Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Post partum blues is a mood swing that happens in post partum mother than often occurs at the third or fourth post partum and peaked between the fifth and fourteenth day. One of the treatment that can be given to post partum mother is by giving relaxation therapy such as Mozart classical music therapy. This study aimed to find the effectiveness of Mozart classical music therapy toward decrease post partum blues symptoms. This study used quasy experimental design with non equivalent control group design. Thirty people were chosen as the sample using purposive sampling technique by focusing on the inclusion criteria. The research instrument used on both group was Edinburgh Postnatal Depression Scale (EPDS) questionnaire sheet which had been tested for its validity and reliability. The analyses used were univariate and bivariate analysis with dependent sample t-test and independent sample t-test. The result of the study showed that the average score of post partum blues symptom in experimental group after having Mozart classical music therapy was 4,93 and for control group which was not given Mozart classical music therapy was 7,80. The statistical result obtained p value of (0,000) < α (0,05), so it can be concluded that Mozart classical music therapy was effective to decrease post partum blues symptom. Based on the result of this study, Mozart classical music therapy was expected to become a part of treatment for mothers with post partum blues. Keywords: Mozart music, post partum blues